Reducing Senior High School Students’ Misconceptions through Inquiry Learning Model on Thermochemistry Material - Erna, Maria; Susilawati, Susilawati; Ramadani, Ramadani (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2020)
Misconception is a serious problem faced by high school students. Through the application of inquiry learning model, this study tries to reduce students' misconceptions, especially on thermochemical material.  The experimental method with the pretest-posttest randomized control group design was used in this study. The samples of the research were 72 eleventh-grade high school students. The inquiry model was applied to the experimental class and the scientific approach was applied to the control class. The three-tier multiple choice with the Certainty of Response Index (CRI) was used to look at misconceptions experienced by the students. The results of the statistical calculation found that the toserved was greater than tcritical. The reduction of misconception categories and the percentage of reduction of misconceptions in the experimental class was 47.53 % in the medium category. Based on the results, it can be concluded that the inquiry learning model helped the students to overcome the misconceptions in thermochemical material. The researcher recommends that the inquiry learning model can be applied to other chemistry materials because their learning can help students find the correct concepts and reduce misconceptions.